Robot that walks ; UTM's first multi-legged mobile robot : design of mechanism for movement ; UTM's multi-legged mobile robot design of on-board controller ; UTM's multi-legged mobile robot : sensing and navigation system ; Robokit : a user friendly graphical research and teaching tool for robot motion tasks / [mikrofilem] - Jayaganthan Krishnan; K. Don Anura Siri; Lim, Wai Hin; Tay, Andrew Soon Heng; Vinesh Kumar Chandrasegaran (Sekudai : UTM, 1996)
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1996